Extracorporeal cardiopulmonary resuscitation for adult patients who underwent post-cardiac surgery. Issue 1 (December 2015) - Zhao, Yanyan; Xing, Jialin; Du, Zhongtao; Liu, Feng; Jia, Ming; Hou, Xiaotong
Abstract Background Refractory cardiac arrest (CA) occasionally develops in patients after cardiac surgery. Objective To examine the clinical outcomes of extracorporeal cardiopulmonary resuscitation (ECPR) in adult patients with post-cardiotomy CA. Methods This was a retrospective study of the 9-year experience (from January 2004 to May 2012) of the Beijing Anzhen Hospital with ECPR in adult patients with post-cardiotomy CA. At this hospital, a dedicated ECPR team is available 24/7 for emergency cases requiring ECPR. Demographic data, biochemical data, survival, morbidity, and complications were examined before, during, and after ECPR. Outcomes were compared between survivors and non-survivors. Results Twenty-four adult patients (19 men and 5 women; mean age: 59.3 ± 11.9 years) received ECPR support for post-cardiotomy CA. The cardiac surgery procedures included coronary artery bypass grafting (n  = 20, 83.3 %), valvular surgery alone (n  = 2, 8.3 %), and correction of congenital heart defects (n  = 2, 8.3 %). The mean extracorporeal membrane oxygenation (ECMO) duration was 115.23 ± 70.17 h. Twenty-one patients received ECPR after intra-aortic balloon pump, and three patients received ECPR directly. The main cause of mortality was multiple system organ failure (n  = 12, 50.0 %). Approximately one-half of non-survivors had severe neurologic impairments. Among 16 patients who were weaned off ECMO support, eight patients survived to hospital discharge. Conclusions ECPR can be effective for partial cardiopulmonary support to resuscitate adult patients suffering from refractory CA after cardiac surgery. Improvement in outcomes of patients who received ECPR requires a multidisciplinary approach to protect organ function and limit organ injury before and during cardiac support.